Analisa Investasi Pemilihan Hydraulic Exavator Dengan Pertimbangan Aspek Teknis Dan Ekonomis - Partawijaya, Yan; Hamid, Desmon; Mukhlis, M; Atmaja, Jajang; Faris F, Muhammad (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2019)
The ownership of heavy equipment is one of the most interesting business at this time, because the indonesian government is actively developing infrastructure, mining, plantation and agriculture sectore. So, it will be very profitable to do this heavy equipment business if it followed an accurate investment analysis. In this research, researchers took a case study on analyzing the selection of hydraulic excavator from 5 different brands, its Komatsu, Hitachi, Caterpillar, Kobelco and Hyundai with 3 different classes (economical, medium and high mode).This research was conducted by collecting primary data (interviews and field surveys) and secondary data (previeos research journal and literature studies) as supporting data. Data processing with reference to Permen PU no.11/PRT/M/2013. Decision making analysis is based on calculation of Nett Present Value (NPV) method, Internal Rate of Return (IRR) method and Break Event Point (BEP) method. After conducting the research, researcher concludes as follows : in the economical class, researcher recommends CAT 313D2 to be invested for the purpose of being rented or used alone. In the medium class, researcher recommends Kobelco SK 200-10 to be invested for the purpose of being rented. In the high mode class, researcher recommends Kobelco SK 330 to be invested for the pupose of being rented. The recommendation that the researcher describes are not absolute decisions to be followed and only as a consideration for investors.